Integrative Educational Strategies for the Promotion of Inclusion. - Villegas González, Crisálida Victoria (Conexiones UG, 2025)
The presentation reflects on integrative educational strategies to promote inclusion, understood as a complex notion, in permanent evolution. Integrative and inclusive strategies materialize the contributions of a variety of theories and models, which seek the comprehensive development of all dimensions of people. It is the product of a documentary study based on the review of texts related to the subject. As results, information is obtained about some strategies that are generally considered integrative and inclusive, such as Universal Learning Design (UDA), Flipped Classroom (FLIP), Problem-Based Learning (ABp) and Project-Based Learning (PBL), as well as the need for permanent updating of teachers. It is concluded that integrative and inclusive educational strategies must be based on the complementarity of three fundamental principles: diversity (difference), equity (equality) and participation (right of all).